Mapping interests in the tuna fisheries of the Western and Central Pacific Ocean. (15th October 2021) - Azmi, Kamal; Hanich, Quentin
Abstract: Fisheries for highly migratory fish stocks are complex, featuring multiple species targeted by different gear types across several national jurisdictions and high seas areas. They require effective cooperation to manage sustainably, typically through a regional fisheries management organisation (RFMO). However, diverse interests in different species and gear types among participating states and fishing entities, many of which are developing, mean that cooperation can be difficult to achieve, with severe consequences for fish stocks, the economies of states with an interest in those stocks, and the livelihoods of communities that depend on them. The Western and Central Pacific Fisheries Commission (WCPFC) manages some of the world's largest tuna fisheries and exemplifies these challenges. We argue that a prerequisite for effective cooperation is an understanding of the interests of each participant in each species and gear type to ensure that conservation and management measures take into account the differential impacts on each one, including whether measures place a disproportionate burden on developing states. This paper uses catch value data for four key tuna species of the WCPFC convention area to illustrate the diversity of interests of participants in these fisheries, with a view to enhancing delegations' understanding of those interests and to inform more effective cooperation. Graphical abstract: Image 1 Highlights: Cooperation between interested states is essential for the sustainable management of highly migratory fish stocks Diversity of interests among coastal and flag state participants is a significant obstacle to agreement on effective conservation and management measures The Western and Central Pacific tuna fisheries exemplify these challenges Understanding that diversity is essential to advancing the sustainability of shared fish stocks, including with respect to the interests of developing countries.